Antiresorptive-associated spontaneous fractures of both tibiae, followed by an atypical femur fracture during the sequential treatment with alendronate, denosumab then teriparatide. Issue 7 (23rd July 2019) - Tan, Juan; Sano, Hiroshige; Poole, Kenneth
Abstract : A 35-year-old man with juvenile idiopathic arthritis since childhood presented with bilateral atypical tibial fractures, followed by a later, single atypical fracture of the femur. The fractures were associated with 6 years of oral alendronate treatment immediately followed by subcutaneous denosumab therapy and later teriparatide therapy for osteoporosis. Atypical fractures are known to occur in the femur following bisphosphonate therapy; however, there are only a few documented cases of atypical fractures in the tibia. Our case highlights a rare but serious complication of a commonly prescribed antiresorptive agent. It also shows that teriparatide, while helpful in increasing bone mass, does not fully prevent the development of atypical fractures. Careful investigation should be considered in patients on long-term antiresorptive therapy presenting with bony tenderness to exclude an atypical fracture.